Numerical simulation of shock response of steel-concrete composite panels - Anandavalli, N.; Lakshmanan, N.; Knight, G. M. Samuel; Rajasankar, J. (Journal of Structural Engineering, 2024)
Response of structures to shock loads differs from that to other loads, primarily due to the impulsive nature of loading. It is important to understand the behaviour of structures for shock loads to arrive at an economical and safe design. Steel-concrete panels combine advantages of both steel and concrete and its application in blast resistant construction is promising. In this paper, a steel- concrete composite panel with through-through connectors is analysed for air blast loading. A simplified approach is used to model the panel. Nonlinear transient dynamic analysis is carried out. Validation of the model is done with an analytical procedure available in literature.